Topical Drug Delivery of Anti-infectives Employing Lipid-Based Nanocarriers: Dermatokinetics as an Important Tool - Thakur, Kanika; Sharma, Gajanand; Singh, Bhupindar; Katare, Om P. (Current Pharmaceutical Design, 2018)
Background: The therapeutic approaches for the management of topical infections have always been a difficult approach due to lack of efficacy of conventional topical formulations, high frequency of topical applications and non-patient compliance. The major challenge in the management of topical infections lies in antibiotic resistance which leads to severe complications and hospitalizations resulting in economic burden and high mortality rates. Methods: Topical delivery employing lipid-based carriers has been a promising strategy to overcome the challenges of poor skin permeation and retention along with large doses which need to be administered systemically. The use of lipid-based delivery systems is a promising strategy for the effective topical delivery of antibiotics and overcoming drug-resistant strains in the skin. The major systems include transfersomes, niosomes, ethosomes, solid lipid nanoparticles, nanostructured lipid carriers, microemulsion and nanoemulsion as the most promising drug delivery approaches to treat infectious disorders. The main advantages of these systems include lipid bilayer structure which mimics the cell membrane and can fuse with infectious microbes. The numerous advantages associated with nanocarriers like enhanced efficacy, improvement in bioavailability, controlled drug release and ability to target the desired infectious pathogen have made these carriers successful. Conclusion: Despite the number of strides taken in the field of topical drug delivery in infectious diseases, it still requires extensive research efforts to have a better perspective of the factors that influence drug permeation along with the mechanism of action with regard to skin penetration and deposition. The final objective of the therapy is to provide a safe and effective therapeutic approach for the management of infectious diseases affecting topical sites leading to enhanced therapeutic efficacy and patient-compliance.
Keywords: Microemulsion